INTEGRATION OF BENCHMARKING INTO THE ARCHITECTURE OF SUSTAINABLE DEVELOPMENT MANAGEMENT: MACRO, MESO, AND MICRO LEVELS (INNOVATIVE ECONOMY, 2026)
Kramarchuk S.P., Babiak H.P. INTEGRATION OF BENCHMARKING INTO THE ARCHITECTURE OF SUSTAINABLE DEVELOPMENT MANAGEMENT: MACRO, MESO, AND MICRO LEVELSPurpose. The aim of this article is to theoretically substantiate and develop a conceptual approach to integrating benchmarking into the architecture of sustainable development management at the macro, meso, and micro levels. The research focuses on ensuring the alignment of economic, social, and environmental objectives, enhancing the effectiveness of strategic decisions, adapting advanced international practices.Methodology of research The study employs a set of general scientific and specialized methods, including induction and deduction for generalizing statistical and analytical data and identifying sustainable development patterns; analysis and synthesis for examining modern approaches to multi-level management and benchmarking integration; abstract and logical method for formulating theoretical conclusions; system approach for considering the national economy as a holistic multi-level system.Findings. The study demonstrates the necessity of transitioning from fragmented sustainable development management to a systemic conceptual approach to benchmarking integration, which ensures alignment of strategic objectives and indicators across macro, meso, and micro levels. Principles for organizing multi-level interaction, structural elements of management architecture, feedback mechanisms, and coordination tools are proposed, enabling improved effectiveness of managerial decisions, facilitation of best practice identification, and adaptation of international experience.The principles of organizing multi-level interaction, structural elements of management architecture, feedback mechanisms and coordination tools are proposed, which allow to increase the effectiveness of management decisions, promote the identification of best practices and adaptation of international experience.Originality. For the first time, a conceptual approach to integrating benchmarking into the multi-level architecture of sustainable development management is formulated, combining principles of goal alignment, indicator systems, and interaction mechanisms across macro, meso, and micro levels. The scientific approach to multi-level sustainable development management is refined in the context of post-war recovery and long-term economic growth of Ukraine.Practical value. The conceptual approach can be applied by government authorities, regional administrations, and enterprises for the development, monitoring, and adjustment of sustainable development strategies, building systems of sustainability indicators, improving ESG strategies, and enhancing the effectiveness of management during post-war recovery processes.Key words: sustainable development, multi-level management, benchmarking, conceptual approach, macro, meso, and micro levels, ESG, integration, post-war recovery, goal alignment.
Keywords: sustainable development; multi-level management; benchmarking; conceptual approach; macro, meso, and micro levels; ESG; integration; post-war recovery; goal alignment